Development of a Watershed Management Plan to Protect Soil and Water Resources, Case of Imady Region Amoron’ny Mania - Razafindrazanakolona A.D.; Robijaona Rahelivololoniaina B.; Rakotonirina M.D.L.; Koto-Te-Nyiwa Ngbolua; Rabesiaka R. (Budapest International Research and Critics University, 2023)
Unsustainable development has often threatened watershed ecology in many parts of the world, and population growth has played a major role in this process. Our study consists of the development of a watershed management plan. The degradation of environments by bushfire, timber exploitation, and firewood harvesting dew soil and pollutes spring water, in addition, there are also negative impacts on the physicochemical property of the soil. This research aims to put in place a watershed management plan to restore the soil and the soil pit against erosion. The development also allows for the protection of water resources and the pollution generated by this degradation. The study specifies the physical characteristics of the watershed: altitude, slope, and constant of Graveluis. We also examine the physicochemical properties of the soil: structure, texture, and pH. After the study of the soil, we also determined the measure of the flow of the source, the organoleptic analysis, and also the physicochemical and bacteriological analysis. The results of this work once made available to the authorities of the basic data could be exploited in the framework of the improvement of the quality of water intended for human consumption. To fight against water pollution, the easiest measure to apply is a large awareness campaign.